PENGGUNAAN BAHASA INDONESIA DALAM SURAT DINAS DI INSTANSI PEMERINTAH DESA SEMAMBUNG KECAMATAN GEDANGAN KABUPATEN SIDOARJO PERIODE SEPTEMBER-OKTOBER 2018 - Windy Kusumaning Tyas; Taufik Nurhadi (Universitas PGRI Adi Buana Surabaya, 2019)
This study aims to describe the form of misuse of words in making official letters. The research data is based on the type of official letter that entered the Semambung Village Government in 2018. Data analysis was divided into two types, namely primary and secondary data. Primary data in this study is written data about language errors, namely errors in the form of word accuracy, word correctness, writing errors, generality, and word efficiency.The method used in this study, namely a qualitative approach. Data from this study are in the form of words. The source of the data in this study is official letters that are included in the government agency of Semambung Village, Gedangan District, Sidoarjo Regency in 2018. Data collection techniques in this study use note-taking techniques. Based on the results of data analysis there are errors in the use of Indonesian in official letters entered by the Semambung Village Government in Gedangan District, Sidoarjo Regency in 2018. In this study it can be concluded that language errors in the form of deviations in the form of errors in word accuracy, word rigidity, economics, subtlety and meaning.